2019
DOI: 10.1194/jlr.m091132
|View full text |Cite
|
Sign up to set email alerts
|

Acid sphingomyelinase deficiency protects mitochondria and improves function recovery after brain injury

Abstract: Traumatic brain injury (TBI) is one of the leading causes of disability worldwide and a prominent risk factor for neurodegenerative diseases. The expansion of nervous tissue damage after the initial trauma involves a multifactorial cascade of events including excitotoxicity, oxidative stress, inflammation and deregulation of sphingolipid metabolism that further mitochondrial dysfunction and secondary brain damage. Our studies establish a fundamental role of acid sphingomyelinase (ASM) in the multi‐faceted mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 89 publications
0
21
0
Order By: Relevance
“…In addition, brain injury triggers increasing in NLRP3 and caspase-1 expression, which is significantly attenuated in ASMdeficient or pharmacologically inhibited mice (Novgorodov et al, 2019). This indicates that ASM-ceramide system is an essential factor for assembling and activating the NLRP3 inflammasome complex in neurological inflammatory cascade.…”
Section: Brain Injurymentioning
confidence: 95%
See 2 more Smart Citations
“…In addition, brain injury triggers increasing in NLRP3 and caspase-1 expression, which is significantly attenuated in ASMdeficient or pharmacologically inhibited mice (Novgorodov et al, 2019). This indicates that ASM-ceramide system is an essential factor for assembling and activating the NLRP3 inflammasome complex in neurological inflammatory cascade.…”
Section: Brain Injurymentioning
confidence: 95%
“…This difference in pH reflects the fact that the ASM gene generates two distinct forms of the proteins: secretory ASM (S-ASM) found extracellular and lysosomal ASM (L-ASM) locating in the endo-lysosomal vesicles. Two forms of ASM are resulted from alternative trafficking and posttranslational modification and trafficking of the encoded protein (Ni and Morales, 2006;Wahe et al, 2010;Vazquez et al, 2016). Trafficking of ASM to lysosome is required for clustering of lipid raft in endothelial cells and their function (Jin et al, 2008).…”
Section: Hydrolysismentioning
confidence: 99%
See 1 more Smart Citation
“…After TSCI, tissues in the spinal cord induce selfdestructive mechanisms termed secondary damage (Romanelli et al, 2019;Pelisch et al, 2020). The main mechanisms of secondary damages after TSCI are excitotoxicity, excessive free radical production, inflammation, and apoptosis (Diaz-Ruiz et al, 2009;Novgorodov et al, 2019). Studies that have focused on reducing neuroinflammation by promoting neuron survival and axon outgrowth have shown some satisfactory therapeutic efficacy (Sun et al, 2018;Lima et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Mice with ASMase deficiency are animal models for human type A or B Niemann–Pick disease, which is a lysosomal lipid storage disease characterized with hepatosplenomegaly and neurological symptoms (Schuchman & Wasserstein, ). In addition to the studies on the pathogenesis of human type A or B Niemann–Pick disease, mice with ASMase deficiency have been also used as animal model by a large number of studies to define the role of ASMase in human inflammatory diseases (Becker et al, ; Beckmann et al, ; von Bismarck et al, ; Boini, Xia, Koka, Gehr, & Li, ; Chung et al, ; Dannhausen et al, ; Dhami, He, & Schuchman, ; Hoehn et al, ; Ikegami, Dhami, & Schuchman, ; Nakatsuji, Tang, Zhang, Gallo, & Huang, ; Novgorodov et al, ; Opreanu et al, ; Osawa et al, ). Interestingly, while most of these studies demonstrated that ASMase deficiency attenuated inflammation (Becker et al, ; Beckmann et al, ; von Bismarck et al, ; Boini et al, ; Chung et al, ; Dhami et al, ; Hoehn et al, ; Nakatsuji et al, ; Novgorodov et al, ; Opreanu et al, ), a few studies showed that ASMase deficiency enhanced inflammation (Dannhausen et al, ; Ikegami et al, ; Osawa et al, ).…”
Section: Introductionmentioning
confidence: 99%